MicroRNA-143/-145 in Cardiovascular Diseases. (28th June 2015) - Zhao, Wang; Zhao, Shui-Ping; Zhao, Yu-Hong
Abstract : MicroRNAs (miRNAs) play an essential role in the onset and development of many cardiovascular diseases. Increasing evidence shows that miRNAs can be used as potential diagnostic biomarkers for cardiovascular diseases, and miRNA-based therapy may be a promising therapy for the treatment of cardiovascular diseases. The microRNA-143/-145 (miR-143/-145) cluster is essential for differentiation of vascular smooth muscle cells (VSMCs) and determines VSMC phenotypic switching. In this review, we summarize the recent progress in knowledge concerning the function of miR-143/-145 in the cardiovascular system and their role in cardiovascular diseases. We discuss the potential role of miR-143/-145 as valuable biomarkers for cardiovascular diseases and explore the potential strategy of targeting miR-143 and miR-145.